PENGARUH SEKTOR PERTANIAN, SEKTOR PERDAGANGAN DAN SEKTOR JASA TERHADAP PRODUK DOMESTIK REGIONAL BRUTO DI KABUPATEN DELI SERDANG - Fatona Naibaho, Yuki; Lubis, Anggia Sari (Program Studi Manajemen Fakultas Ekonomi dan Bisnis, Universitas Muslim Nusantara Al-Washliyah, 2023)
This study aims to determine the effect of the agricultural sector, trade sector, and service sector on the Gross Regional Domestic Product in Deli Serdang Regency. This type of research is a quantitative descriptive study, where the data used is secondary data obtained from BPS Deli Serdang Regency. The analytical method used is multiple linear regression, using 12 reviews to find out how the independent variable influences the dependent variable. After testing, the results show that the agricultural sector has a significant effect on Gross Regional Domestic Product in Deli Serdang Regency, the trade sector also has a significant effect on Gross Regional Domestic Product in Deli Serdang Regency, and the service sector also has an effect on Gross Regional Domestic Product in Deli Serdang Regency. From the statistical test results, the value of Fcount > Ftable was obtained, namely (42.06520 > 4.76). Likewise simultaneously or jointly the relationship between the independent variables (Agriculture Sector, Trade Sector, and Service Sector) has a significant effect on the bond variable (Gross Regional Domestic Product) in Deli Serdang Regency.